Ultrasonographic analysis of the hyoid bone distance in individuals with neurogenic oropharyngeal dysphagia - Bragato, Simone Galli Rocha [UNESP]; da Silva, Roberta Gonçalves [UNESP]; Berti, Larissa Cristina [UNESP] (FapUNIFESP (SciELO), 2024)
To compare the ultrasound measurement of distance from the approximation of the hyoid bone during of the maximum deglutition peak between healthy individuals and neurogenic dysphagic individuals and to verify the effect of food consistencies on the displacement of the hyoid bone. Prospective, controlled clinical study. Ultrasound recordings of the oropharyngeal deglutition were conducted in 10 adults diagnosed with oropharyngeal dysphagia and in 10 healthy adults, matched by sex and age group. A portable ultrasound model Micro ultrasound system with a microconvex transducer 5-10 MHz, coupled to a computer as well as the head stabilizer were used. The ultrasound images were recorded using the AAA software (Articulate Assistant Advanced) at a rate of 120 frames/second. Food consistencies level 0 (free volume and 5 mL) and level 4 (5 mL) were used, based on the International Dysphagia Diet Standardisation Initiative (IDSSI). The calculation of the mean and standard deviation was used for the descriptive analysis, while the repeated measures ANOVA test was used for the inferential analysis. Results showed dysphagic individuals had lower elevation of the hyoid bone marked by a longer distance from the approximation of the hyoid bone during of the maximum deglutition peak when compared to healthy individuals, regardless of the food consistency offered. It was concluded that the ultrasound measurement of distance from the approximation of the hyoid bone during of the maximum deglutition peak showed less laryngeal elevation in individuals with neurogenic oropharyngeal dysphagia when compared to healthy individuals for all food consistencies offered.
Análise ultrassonográfica da distância do osso hioide em indivíduos com disfagia orofaríngea neurogênica
Keywords: Deglutition; Deglutition Disorders; Hyoid Bone; Ultrasonics; Ultrasonography